The potential of Grateloupia filicina (Lamouroux) J. Agardh. for mariculture: culture experiments and observations on shore phenology - Vetter, Susanne (Department of Biological Sciences, 2017)
Grateloupia filicina is a carrageenophytic red alga which is in demand as a carrageenan raw material and for use in food. There is therefore interest in developing a technique for mariculturing this species. Since vegetative propagation from thallus fragments has not been successful, the present study was initiated to determine suitable conditions for spore liberation and growth of G. filicina from spores. It was also attempted to propagate G. filicina sporelings from crust and thallus fragments. In addition, the proportions of plants in different life history phases were determined in August and September to test for seasonal differences in shore phenology, and whether G. filicina is monoecious or dioecious, since there is disagreement on this in the literature. Spore release was easy to achieve, even without stressing the parent plant. Growth of crusts was found to be fastest at 50 μM.m⁻².s⁻¹ and at 20°C. Carposporelings (i.e. young tetrasporophytes) grew slightly but significantly faster than tetrasporelings (i.e. young carposporophytes). Crust fragments were able re-attach to the substrate and gave rise to new upright thalli within 1-2 weeks, compared to 4-5 weeks between spore release and thallus initiation. Attachment was weak, however, and only a small proportion of the crust fragments placed into culture regenerated. Thallus regeneration was not successful. There were seasonal differences in shore phenology during the study period: while two thirds of the plants collected in August were carposporophytes, only tetrasporophytes were found in September. No male gametophytes or spermatangia were found. It did not emerge from this study whether G. filicina in an annual, or what phenotypic differences are found throughout the year. Information of this kind is important for mariculture as it affects the supply of parent plants (and therefore spores) and the growth of young plants on ropes if these are released into the sea. The culturing experiments look promising; techniques (seeding ropes directly with spores or using regenerated crust fragments) still need to be refined.